ANALISIS PENERAPAN LITERASI MEMBACA PADA PEMBELAJARAN SOSIOLOGI DI SMAN 1 PULAU MAYA - Dayang Sumbi; Izhar Salim; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to get information about the application of reading literacy and its inhibiting factors in sociology learning at SMAN 1 Pulau Maya. The approach used in this research was qualitative method with descriptive analysis. The techniques used to obtain data in this research were observation technique, interview, and documentation study, while the tools of collecting data wee observation guide, interview guide, documentation, and camera.. The result showed that the application of reading literacy already applied in sociology learning at SMAN 1 PulauMaya, but it had not applied maximally yet, the cause was from total 10 indicators, only 7 indicators applied, some of the unapplied indicators were students had not have reading journal, school had not involving public like parents and alumnus in literacy application, and also there was no commitment from school in emphasizing another literacy activities, no reading corner in classrooms, whereas reading corner is one of the important indicators in supporting the application of reading literacy. The inhibiting factors of reading literacy were: (a) the lackness of reading interest from students, (b) no school policy which emphasizing GLS because in need of adaptation toward 2013 curriculum, (c) the lackness of school facilities like reading corners, book references, and internet access for students. Keywords: Reading Literacy, Sociology Learning